Activities for women in the spirit resolution of the Party’s XIII Congress - Bùi Thị Bích Thuận (Tạp chí Nghiên cứu Khoa học Công đoàn, 2022)
During the revolutionary process, our Party always cared about leading activities for women. At the same time, the State has also issued many policies and legal documents to create conditions for women to develop and promote gender equality. The Resolution of the 13th Party Congress gave important orientations to activities for women in order to promote their roles and aspirations to rise and build up Vietnamese women in the new era; improve the quality of female human resources, meet the requirements of sustainable development and international integration; take care of and protect women, and support women in difficult circumstances, ethnic minorities and mountainous people.